THE EFFECT OF FINANCIAL LITERACY ON FINANCIAL WELL-BEING MEDIATED BY FINANCIAL BEHAVIOR - Bangun Putra Prasetya (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The occurrence of a shift in the consumption patterns of people who originally shopped in traditional markets to modern markets. Market traders often experience delays in development that can affect financial well-being (Financial Well Being). This study aims to see the effect of financial literacy on financial well-being mediated by financial behavior Design/methodology/approach: This research is a quantitative research using the PLS SEM analysis tool. This research was carried out in Kotagede market, which was established since the time of the Mataram Kingdom in Yogyakarta. The research sample was 99 traders in Kotagede market, Yogyakarta. Findings: The results showed that there was an influence of Financial Literacy variables on Financial Behavior variables and Financial Behavior variables on Financial Well Being. While the influence between Financial Literacy variables on Financial Well Being is stated to be insignificant. But the results show that the difference between the effect of financial literacy on financial well being will be significant if mediated by financial behavior